(untitled) (International Journal of Ayurveda and Pharma Research, 2015)
A married female patient of 31 years attended the OPD with the complaint of increased duration of menstruation associated with excessive flow. She gave history of medication (Hormonal therapy) twice for three consecutive months. But, patient was not satisfied by the treatment as no symptomatic relief was attained and it was affecting her daily routine. With the aim to minimize the cyclic blood loss and regularize the cycle, the Shodhana chikitsa (detoxification) i. e. Virechana karma and Shamana chikitsa (palliative treatment) with Pushyanuga churna, Lodhra churna, Chanderprabhavati, Punarnava mandoor and Ashokarishta was advised to the patient for three consecutive cycles. This therapy, helped to cure the heavy flow during menses and regularize the cycle. But to establish this fact, further study of longer duration and on larger sample is required.